(S)-2-Hydroxyisovalerate Production from d-Xylose with CO-Converting Clostridium ragsdalei - Irina Schwarz; Markus Rupp; Oliver Frank; Andreas Daschner; Dirk Weuster-Botz (Fermentation)
Clostridium ragsdalei was found to produce (S)-2-hydroxyisovalerate (2-HIV) as a novel product in addition to acetate, ethanol, and d-2,3-butanediol in heterotrophic (d-xylose), autotrophic (CO), and mixotrophic (d-xylose + CO) conditions. Mixotrophic batch processes in stirred-tank bioreactors with continuous gassing resulted in improved production of this alpha-hydroxy acid compared to batch processes solely with either d-xylose or CO. The maximal CO uptake rate was considerably reduced in mixotrophic compared to autotrophic processes, resulting in a concomitant decreased total CO2 production. Simultaneous conversion of 9.5 g L−1 d-xylose and 320 mmol CO enabled the production of 1.8 g L−1 2-HIV in addition to 1.1 g L−1 d-2,3-butanediol, 2.0 g L−1 ethanol, and 1.8 g L−1 acetate. With reduced initial d-xylose (3.1 g L−1), l-valine production started when d-xylose was depleted, reaching a maximum of 0.4 g L−1 l-valine. Using l-arabinose or d-glucose instead of d-xylose in mixotrophic batch processes reduced the 2-HIV production by C. ragsdalei. Considerable amounts of meso-2,3-butanediol (0.9–1.3 g L−1) were produced instead, which was not observed with d-xylose. The monomer 2-HIV can form polyesters that make the molecule attractive for application as bioplastic (polyhydroxyalkanoates) or new composite material.